The Influence of Regional Original Income and Balanced Funds on Capital Expenditure and Community Welfare - Arif, Supriadi; Mallongi, Syahrir; Selong, Abbas (Jurnal Ekonomi Balance, 2024)
This study examines the influence of Regional Original Income (ROI) and Balancing Funds (BF) on Capital Expenditure (CE) and Community Welfare (CW) in Makassar City, South Sulawesi Province. Using secondary data from the BPS covering the period from 2014 to 2023, the research applies quantitative methods, including multiple linear regression and hypothesis testing, to analyze the relationships between these variables. The findings indicate that ROI significantly and positively impacts CW, suggesting that higher ROI contributes to improved community welfare. In contrast, BF and CE do not show significant effects on CW within the observed timeframe. This result highlights the critical role of ROI in driving community welfare improvements, emphasizing the need for effective financial management and strategic planning by regional governments. The study underscores the importance of the prudent allocation of regional funds to optimize public services and infrastructure development, which are essential for enhancing overall welfare. It also points out that simply increasing BF or CE without targeted strategies may not yield substantial benefits for community welfare. To achieve a more comprehensive understanding of the factors affecting CW, further research is suggested. Expanding the scope of analysis and including additional variables, such as education, healthcare, and private investment, could provide a deeper insight into the complex dynamics influencing welfare. These findings are expected to guide policymakers in formulating strategies to foster sustainable regional development.